"Mandibulofacial dysostosis with microcephaly" caused by EFTUD2 mutations: Expanding the phenotype1. Issue 1 (14th December 2012) - Luquetti, Daniela V.; Hing, Anne V.; Rieder, Mark J.; Nickerson, Deborah A.; Turner, Emily H.; Smith, Joshua; Park, Sarah; Cunningham, Michael L.
Abstract Heterozygous mutations in the EFTUD2 were identified in 12 individuals with a rare sporadic craniofacial condition termed Mandibulofacial dysostosis with microcephaly (MIM 610536). We present clinical and radiographic features of three additional patients with de novo heterozygous mutations in EFTUD2. Although clinical features overlap with findings of the original report (choanal atresia, cleft palate, maxillary and mandibular hypoplasia, and microtia), microcephaly was present in two of three patients and cognitive impairment was milder in those with head circumference proportional to height. Our cases expand the phenotypic spectrum to include epibulbar dermoids and zygomatic arch clefting. We suggest that craniofacial computed tomography studies to assess cleft of zygomatic arch may assist in making this diagnosis. We recommend consideration of EFTUD2 testing in individuals with features of oculo‐auriculo‐vertebral spectrum and bilateral microtia, or individuals with atypical CHARGE syndrome who do not have a CHD7 mutation, particularly those with a zygomatic arch cleft. The absence of microcephaly in one patient indicates that it is a highly variable phenotypic feature. © 2012 Wiley Periodicals, Inc.